Optical, morphological and durability studies of quaternary chalcogenide Ge-Sb(As)-(S, Te) films. (October 2018) - Dulgheru, Nicoleta; Stoica, Mihai; Calderon-Moreno, Jose Maria; Anastasescu, Mihai; Nicolescu, Madalina; Stroescu, Hermine; Atkinson, Irina; Stanculescu, Ioana; Szekeres, Anna; Gartner, Mariuca
Graphical abstract: Highlights: Films of two glassy chalcogenide systems of Gex -Sb/As40-x -S50 -Te10 were studied. Optical constants as function of films composition are obtained in 0.25–30 μm range. The transparent zone of the films is in the (0.6–2.5) μm spectral range. The vibrational modes were determined from IR-SE, FTIR and Raman. The stability of the films after QT was proved by AFM, SEM and SE analyses. Abstract: Thin films from two glassy systems of Gex Sb40-x S50 Te10 and Gex As40-x S50 Te10, with compositions x = 10, 20 and 27 at. %, were deposited on optical glass substrates by vacuum thermal evaporation of powdered parent chalcogenide glasses. The complex refractive index and dielectric constants of the films are determined by ellipsometry in a wide spectral range of 0.25–30 μm. In the transparent spectral region of 0.6–2.5 μm the refractive index values are within 2.9–2.3 and 3.3–2.4 for the As-contained and Sb-contained films, respectively. From the IR and Raman data analysis the basic chemical and oxygen-related impurity bonds are identified. The films durability properties were established by applying the US Military Standard quality tests. The quality-test-induced-changes in surface morphology were evaluated. The films are relatively stable after quality test treatments, which cause a small degree of densification and surface roughening for Sb-containing films and surface flattening for As-containing ones.